Effects of hydrogen on fatigue behavior of near-alpha titanium alloys. (August 2018) - Sinha, V.; Schwarz, R.B.; Mills, M.J.; Williams, J.C.
Abstract: The influence of hydrogen content on fatigue response was examined for a near- α titanium alloy, Ti-6Al-2Sn-4Zr-2Mo-0.1Si, in bimodal microstructural condition with ~70 vol% primary α . The hydrogen content was varied in the range 7–127 ppm (by weight). The fracture mechanism at crack-initiation sites changed from ductile tearing with localized plasticity in low (<50 ppm) hydrogen alloys to a more brittle fracture with facets in high (≥100 ppm) hydrogen alloys. The variation in fatigue life (by a factor of ≤1.8) was partially associated with the differences in hydrogen level and partially with the statistical scatter in life. Graphical abstract: Unlabelled Image